Clinical and molecular characterisation of hereditary and sporadic metastatic colorectal cancers harbouring microsatellite instability/DNA mismatch repair deficiency. (November 2017) - Cohen, R.; Buhard, O.; Cervera, P.; Hain, E.; Dumont, S.; Bardier, A.; Bachet, J.-B.; Gornet, J.-M.; Lopez-Trabada, D.; Dumont, S.; Kaci, R.; Bertheau, P.; et al.
Abstract: Background: Patients treated with chemotherapy for microsatellite unstable (MSI) and/or mismatch repair deficient (dMMR) cancer metastatic colorectal cancer (mCRC) exhibit poor prognosis. We aimed to evaluate the relevance of distinguishing sporadic from Lynch syndrome (LS)-like mCRCs. Patients and methods: MSI/dMMR mCRC patients were retrospectively identified in six French hospitals. Tumour samples were screened for MSI, dMMR, RAS / RAF mutations and MLH1 methylation. Sporadic cases were molecularly defined as those displaying MLH1/PMS2 loss of expression with BRAF V600E and/or MLH1 hypermethylation and no MMR germline mutation. Results: Among 129 MSI/dMMR mCRC patients, 81 (63%) were LS-like and 48 (37%) had sporadic tumours; 22% of MLH1/PMS2-negative mCRCs would have been misclassified using an algorithm based on local medical records (age, Amsterdam II criteria, BRAF and MMR statuses when locally tested), compared to a systematical assessment of MMR, BRAF and MLH1 methylation statuses. In univariate analysis, parameters associated with better overall survival were age ( P  < 0.0001), metastatic resection ( P  = 0.001) and LS-like mCRC ( P  = 0.01), but not BRAF V600E. In multivariate analysis, age (hazard ratio (HR) = 3.19, P  = 0.01) and metastatic resection (HR = 4.2, P  = 0.001) were associated with overall survival, but not LS. LS-like patients were associated with more frequent liver involvement, metastatic resection and better disease-free survival after metastasectomy (HR = 0.28, P  = 0.01). Median progression-free survival of first-line chemotherapy was similar between the two groups (4.2 and 4.2 months; P  = 0.44). Conclusions: LS-like and sporadic MSI/dMMR mCRCs display distinct natural histories. MMR, BRAF mutation and MLH1 methylation testing should be mandatory to differentiate LS-like and sporadic MSI/dMMR mCRC, to determine in particular whether immune checkpoint inhibitors efficacy differs in these two populations. Highlights: Metastatic colorectal cancers with sporadic or inherited MMR deficiency display distinct natural histories. A algorithm combining MMR protein expression, BRAF mutation and MLH1 methylation is mandatory to properly determine the mechanism of MMR deficiency. A better characterisation of dMMR CRCs is needed to determine whether therapeutic agents efficacy differs depending on the origin of the MMR deficiency.